2021
DOI: 10.36748/ijswc.2.1_20
|View full text |Cite
|
Sign up to set email alerts
|

Incisional Negative Pressure Wound Therapy with Reinforcement of Subcutaneous Drainage (Hybrid-iNPWT)

Abstract: Introduction: Incisional negative pressure wound therapy (iNPWT) is a preventive measure for postoperative wound dehiscence in which negative pressure is applied to the suture wound. Indeed, insufficient drainage in the deep layer is associated with an increased risk of developing subcutaneous hematoma and wound complications. Here, we report two cases of lower limb degloving injury successfully managed by iNPWT, with the reinforcement of subcutaneous drainage (hybrid-iNPWT). Case presentation: Case 1 was that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Until now, relevant large-scale in vivo data is lacking on similarly modified iNPWT dressing as we were the first to consider possible modifications based on clinical expertise. Recently, Kitano et al presented two cases in which they applied a similar iNPWT system with a connected subcutaneous suction drain tube [ 31 ]. They termed the apparatus hybrid-iNPWT and used it for hematoma prevention in degloving injuries of two elderly patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until now, relevant large-scale in vivo data is lacking on similarly modified iNPWT dressing as we were the first to consider possible modifications based on clinical expertise. Recently, Kitano et al presented two cases in which they applied a similar iNPWT system with a connected subcutaneous suction drain tube [ 31 ]. They termed the apparatus hybrid-iNPWT and used it for hematoma prevention in degloving injuries of two elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…We performed the measurements in linear incisions that are straight, nonwinding cavities. In contrast, degloving injuries represent larger, nonlinear wounds, and the hybrid-iNPWT still seemed to ameliorate wound hematoma formation [ 31 ]. Taking together our ex vivo and the scarce existing clinical data, it suggests an efficacy on linear as well as wider wounds by modified iNPWT.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of negative pressure on bone defect repair can be modified by adjusting the working distance and pressure magnitude. As the distance increases, the pressure, shear stress, and fluid velocity of bone trabeculae decrease exponentially, and the magnitude of negative pressure greatly influences fluid dynamics, especially when the pressure is near the pressure source 158 . Moreover, the structural anisotropy of bone trabeculae is associated with the anisotropic hydrodynamic behavior of the marrow, and the stimulation of negative pressure leads to unstable marrow flow during trabecular regeneration.…”
Section: Biophysical Stimulation For Osteoporotic Osseointegration An...mentioning
confidence: 99%
“…The therapy has evolved extensively, including some with a cleaning function 2,3) and others intended mainly for outpatient use. It has additional clinical applications, such as drainage of dead spaces using continuous negative pressure 4) and continuous local perfusion of highly concentrated antibiotics 5) . Recent studies have demonstrated that NPWT is useful for skin graft fixation 6,7) because of advantages such as better stability and drainage of exudate than conventional fixation methods (e.g., tie-over method).…”
Section: Introductionmentioning
confidence: 99%